Advance care planning and clinical decision-making. (December 2022) - Taubert, Mark; Lewis–Williams, Gemma; Muir, David
Abstract: Advance care planning has been defined as a process for individuals with decisional capacity to outline their values and reflect upon the meanings and consequences of serious illness scenarios in the months and years ahead. This process defines goals and preferences for future medical treatment and care, and addresses individuals' views across the physical, psychological, social and spiritual domains. It encourages individuals to identify a personal representative, and to record and regularly review any preferences so that these can be taken into account should they, at some point, be unable to make their own decisions. The internationally agreed definition has not incorporated patients with absent, diminished or fluctuating mental capacity at the time of making a decision about future care. This article discusses some of the clinical implications of this, and illustrates existing examples of best interest decision-making processes via a future care-planning approach. The article also highlights current definitions and discusses the need for a process that is concerned with 'what matters most' to patients, and is therefore not wholly focused on questions about future resuscitation attempts.